Deposition and fabrication of biomaterials using cold spray technique: A review on the application of biomedical-implants - Gaurav Prashar; Hitesh Vasudev (Applied Surface Science Advances, 2023)
Cold spray processing (CS) is an all-solid-state, relatively low-temperature coating method that overcomes the drawbacks of traditional thermal spray methods to enable the spraying of heat and O2-sensitive materials. Defects like phase change, residual stresses and de-bonding are typical when conventional coating methods such as plasma spray for deposition of biomaterials. This review sums up the restrictive method CS used for depositing biomaterials at low temperatures which restricts the formation of oxides; minimize phase changes and introduce compressive residual stresses. Due to these benefits it appears to be on the verge of being competitive with other conventional approaches. The CS technique contributes to improve bioactivity, corrosion resistance, wear resistance and preserve the properties of biomaterials. We attempt to provide a succinct and thorough overview of biomaterials which can be fabricated using CS.